Robust and Imperceptible Spread-Spectrum Watermarking for Telemedicine Applications - Singh A.K.; Kumar B.; Dave M.; Mohan A. (My University, 2025)
This paper presents a new robust and secure digital watermarking scheme for its potential application in Telemedicine. The algorithm embeds medical text watermarks such as patient’s identity, image identity code and doctor’s identity into selected sub-band discrete wavelet transform (DWT) coefficients of the cover medical image using spread-spectrum technique. In the embedding process, the cover image is decomposed up to third level DWT coefficients. Three different text watermarks are embedded into the selected horizontal and vertical sub band DWT coefficients of the first, second and third level respectively. Selection of these coefficients for embedding purpose is based on threshold criteria defined in this paper. Robustness of the proposed watermarking scheme is further enhanced by applying error correcting code to the ASCII representation of the text watermark and the encoded text watermark is finally embedded into the cover medical image. It is found that the proposed scheme correctly extracts the embedded watermarks without error and provides high degree robustness against numerous known attacks while maintaining the imperceptibility of watermarked image. © 2015, The National Academy of Sciences, India.